The Effect of Digital Storytelling implementation on the Second Episode Student's Learning Motivation in Social Studies - Al- Makhmari, Said Rashid Ahmed (Journal of Educational and Psychological Sciences, 2021)
The study aimed to study the impact of cycle two students, (5- 9) employment of the digital stories in social studies. This study will reflect on developing the student learning motivation. In the light of its objectives for experimental approach based on the semi – experimental design of the two groups (experimental & control) and two measurements (pre& post) on a sample of (63) of basic education students from grade nine. Then, the sample was divided on two groups randomly. The experimental group consist of (32) students which taught lessons of social studies by using digital stories while the control group contain (31) students by using traditional method which taught the same content.According to the principles and foundations the study found difference in morale lead statistically at the level of the significance (a < 0.05) between means of sources of the experimental group in the post- test and the control group for all knowledge levels. The total score of the academic achievement of learning motivation scale in favor of experimental group.
Keywords: digital storytelling; motivation; social studies